Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.22541/au.159863421.14865909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Shift Work in Intensive Care on Attention Disorder in Nurses

Abstract: Aim: The purpose of this study is to determine the level of attention between shifts and to make recommendations about the regulation of shifts. Methods:The researchers applied the Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A), Pittsburgh Sleep Quality Index (PSQI) and Stroop color word interaction test (SCWI) in 72 intensive care workers working in different shifts. Result: The study included a total of 72 participants, including 30 (43.3%) females and 42 (58.3%) males. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…According to the regulations and rules in hospitals and the requirements to provide continuous 24‐h service for patient care, the described work schedule (day–night–evening shift, rest) is a typical schedule in general ward, in hospitals from China. In other departments with special requirements, such as emergency department, intensive care unit or operating room, the work schedule may be different from that in general ward, which is also indicated in previously reported studies (Dönmezdil & Araç, 2021; Esmaily et al, 2021; Kaliyaperumal et al, 2017).…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…According to the regulations and rules in hospitals and the requirements to provide continuous 24‐h service for patient care, the described work schedule (day–night–evening shift, rest) is a typical schedule in general ward, in hospitals from China. In other departments with special requirements, such as emergency department, intensive care unit or operating room, the work schedule may be different from that in general ward, which is also indicated in previously reported studies (Dönmezdil & Araç, 2021; Esmaily et al, 2021; Kaliyaperumal et al, 2017).…”
Section: Methodsmentioning
confidence: 88%
“…In addition, it has been well reported that attention and reaction can be greatly impaired by Stroop tests during evening or night shifts (Dönmezdil & Araç, 2021; Esmaily et al, 2021; Kaliyaperumal et al, 2017), and working hours can even last 12 h or more (Dönmezdil & Araç, 2021; Esmaily et al, 2021). In accordance with a previous report, an increase in reaction time was also found after our evening shift, without statistical significance (Esmaily et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations